Climate change worry and the association with future depression and anxiety: cross-national analysis of 11 European countries - Claire L Niedzwiedz; Aminah Collery (BMJ Mental Health)
Background Climate change affects people’s mental health directly and indirectly. Climate anxiety, characterised by persistent worry and distress about environmental changes, is increasingly recognised as a factor affecting mental well-being. This study focused on potential implications of climate change worry for mental health.Objective To assess whether climate change worry is associated with an increased risk of depression, anxiety and sleep disturbance across European countries.Methods The study used longitudinal data from the European Social Survey-10 (2020–2022) and the follow-up CROss-National Online Survey 2 wave 4 (2022). A total of 5155 participants across 11 European countries were included in the analysis. Logistic regression models were used to examine the relationship between climate change worry and mental health outcomes (anxiety, depression and sleep), adjusting for potential confounding factors. Stratified analyses were conducted to assess variations between countries.Findings Climate change worry was associated with increased risk of anxiety (OR: 1.38, 95% CI: 1.13 to 1.68), but not depression (OR: 1.10, 95% CI: 0.94 to 1.29), or sleep disturbance (OR: 1.08, 95% CI: 0.92 to 1.27), in pooled analyses across countries. Country-specific analyses revealed notable differences, with the strongest associations between climate worry and anxiety observed in Slovenia and Italy.Conclusions These findings suggest that the psychological impact of climate change worry is not uniform across Europe and may be influenced by national policies, environmental risks and sociocultural factors. Given the varying effects across countries, policy-makers should consider contextual factors when designing strategies to address climate anxiety. Integrating mental health considerations into climate policies may enhance public engagement and resilience in the face of environmental challenges.Clinical implications Traditional therapeutic approaches may not fully capture the unique distress associated with environmental worries, necessitating the development of specialised interventions that validate individuals’ concerns while equipping them with coping mechanisms.